PERAN SARANA ANGKUTAN UMUM DALAM AKTIVITAS EKONOMI DAN SOSIAL MASYARAKAT DI KOTA PEKANBARU - -, MUTIAULFAH (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
This study aimed to describe the characteristics of public transport as well as its prospects in Kota Pekanbaru; explained the role of public transport in economic and social activities in Pekanbaru; and described the profile of public transportationpassenger as well. This study used a survey approach with descriptive methods. Population in this study wasthe urban communities in Kota Pekanbaru who use public transportation services in their daily activities.Sample for this research was determined by cluster technique sampling which conducted with a sample of 10 respondents from each district, therefore the total sample were 120 respondents. Questionaires and Interview guidelines was used in term of data collection technique. The qualitative data was analyzed using statistical techniques known as nonparametric Spearman's Rho correlation and othersbasic statistical tests running with SPSS for Windows. Based on the result of these study, viewed by public transportation route, there is a bigger chance for development on public transportation management in Kota Pekanbaru related to the large number of population and the size of thearea itself. But one thing needs to be fixedis the route management system; to minimize the overlapping routes in the future. Spearman’s Rho test results showed that the role of public transport on economic and social activities in Pekanbaru was positive and significant, with0,334 correlation coefficient for economic activities, and by 0,404 for social activities. From the data collected, it is known that people who use public transport services were not only the low-income level, the procurement of BRT / Trans Metro Pekanbaruhad been proved to changes the preference of most citizen to use public transport rather than private vehicles as their daily mobility tools.